Relationship between the Level of Knowledge and Education of Mothers Regarding Fever Management in Children 1-5 Years: A Cross-sectional Study - Sumantri, Apria Wilinda (STIKes Al-Ma'arif Baturaja, 2025)
Fever is one of the common health problems in children under five that can cause serious complications if not treated appropriately. Maternal knowledge and education level are important factors in determining the quality of fever management in children. This study aims to analyze the relationship between the level of knowledge and education of mothers with fever management in children aged 1-5 years. This study used a cross-sectional design with a total of 30 maternal respondents who had children aged 1-5 years and visited the Penyandingan Health Center in January 2025. Total sampling technique was used, and data were collected through questionnaires and checklists. Bivariate analysis was performed using the Chi-Square test with a significance value of α = 0.05. The majority of respondents (70%) had good knowledge, and 63.3% of mothers performed fever management correctly. There was a significant relationship between maternal knowledge and fever management (p = 0.004), and between maternal education and fever management (p = 0.002). Maternal knowledge and education were significantly associated with the quality of fever management in children. Continuous educational interventions are needed for mothers of toddlers to improve knowledge and skills in fever management to prevent complications in children.